Robotic-Assisted Percutaneous Coronary Intervention Through Transradial Approach: Experience in 4 Patients with Complex Lesions - Anuwatworn, Amornpol (Tex Heart Inst J, 2020)
Robotic-assisted percutaneous coronary intervention can reduce the exposure of interventional cardiologists to radiation and minimize the risk of occupational orthopedic injuries from wearing heavy protective aprons. The PRECISE (Percutaneous Robotically-Enhanced Coronary Intervention) study showed the efficacy and safety of robotic-assisted procedures for relatively low-risk lesions in single coronary arteries. Several reports have described robotic-assisted treatment of complex high-risk lesions, mostly through the transfemoral approach. We report 4 cases of patients in whom we used the transradial approach to treat complex lesions in the left anterior descending coronary artery with bifurcation balloon angioplasty reconstruction (2 cases), in the ostium of the first diagonal branch, and in the right coronary artery.